Webster's New World student's dictionary - Goldman, Jonathan, 1944-; Sparks, Andrew N. (New York, NY : Macmillan USA, 1996)
Designed for students in grades five through eight, this illustrated dictionary of the English language contains more than 50,000 definitions as well as pronunciation guides, word origins, synonyms, maps, and other features.
"This book was previously titled: Webster's New World dictionary for young adults"--Publisher's info.
Wilson's Junior High School.
5-8
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries; English language -- Dictionaries